Sub National Collaboration In Increasing Global Competitiveness: Existence For Actors Cross-Border In Riau Islands - Munir, Fitrisia; Prayuda, Rendi; Yudilla, Artha (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
International activities by sub-state actors today do not only apply to developed and developed democratic states, but extend across borders between countries and regions. Along with the rapid wave of globalization, there is a demand for the role of sub-state actors to create various actions in international relations. This study empirically assesses the chance of sub-state actors in the study of international affairs by using inter-state local government collaboration as an expressive action that must be performed between countries, particularly across borders. The success of sub-state actors will not only be an effective tool to solve problems in crossing borders, but also to ensure sustainable living and economic development regionally in the future. This study discovered that improving the capabilities of sub-state actors in cross-border competition can improve the collaboration of local governments between countries in order to overcome various problems that arise. In addition, this research affirms the importance of cross-border local government collaboration as an action to realize the emancipation of the nation-state monopoly in public action to synchronize the interests of all actors in international cooperation. Keywords: Collaborative Sub-national, Cross-border , Sub-State Actors.